Effect Of Heat And Time On A 5 Kg Capacity Clothes Dryer Machine - Boki, Meki Alfonsus Ferdinan; Muharom, Muharom; Riyadi, Slamet; Siswadi, Siswadi; Setyono, Gatot (Journal of System Engineering and Technological Innovation, 2024)
Utilization of natural energy sources such as solar thermal energy and geothermal energy converted into electrical energy through appropriate technology has been widely used and cannot be separated from the climate. One of them is the process of drying clothes. The drying process used by many people is still simple, namely by drying directly under the sun. This method is less effective because it takes a long time and still depends on the weather. So from here, we will innovate in making a clothes dryer that uses a heating element as a heat source and a fan. The purpose of using a heating element and fan is to help speed up the process of drying clothes in a short time without having to wait a long time and to be able to control the temperature of clothes.